O processo de construção e inauguração da Mesquita de Cuiabá em jornais impressos : uma perspectiva da linguística aplicada indisciplinar - Silva, Adriana Auxiliadora da (2020)
This investigation is connected to the Languages and Decolonialities Research Group (GPLED) of the Postgraduate Program in Language Studies at the Federal University of Mato Grosso in the line of research “Textual and Discursive Practices: Multiple Approaches”. The objective of this dissertation is to analyze how the meanings about the construction and inauguration of the mosque in Cuiabá were constructed in the reports of printed newspapers, in order to verify how the process of appreciation of this religious temple was presented. The research has a qualitative approach with fundamental reference in Denzin and Lincoln (2006). Then, I explain the assumptions of documentary and interpretative research based on Fonseca (2002), Zolin Vesz (2015) apud Rojo (2013) under the perspective of Indisciplinary Applied Linguistics (MOITA LOPES, 2006). Undisciplined applied linguistics has brought an interdisciplinary look to research, in which Language dialogues with Humanities, to understand the meanings established in the reports' speeches. The theoretical framework is separated in two parts: in the first part, I approach the socio-historical formation of Islam and the questions of the Muslim organization as State and Religion anchored in Said (2007), Pinto (2010; 2014), Sahd (2011), Bissio (2012), Demant (2015); in the second part, I present the 'master narrative' about Arab migration (PINTO, 2010), in addition to other authors working in this area, such as Brandão (2007), Truzzi (2007), Said (2007), Karam (2009), Demant (2015 ), Zolin Vesz (2015, 2016a, 2016b), Barreto (2017), Fernandes (2018) and Campos (2019), who discuss the Arab migration to the Americas, the expulsion of the Arab people from the Middle East, the reception and social integration of this migrant in the Americas, in order to detail the occurrence of the latter in some cities in Brazil and in Cuiabá. The questions that guided the research were: 1st. How are the construction and inauguration of the mosque described in the newspapers Diário de Cuiabá, O Estado de Mato Grosso, Jornal Equipe, O Jornal de Mato Grosso? 2nd. How can the description of the construction and inauguration of the mosque contribute to understanding the process of Arab migration in Cuiabá? The work also intends to reveal in Basic Education that the presence of the other, in the case of the Arab people, does not refer, in our city, to the discourses of violence and terror that are regularly linked to one another in the media. The analysis of the reports suggests that the process of appreciation of the Muslim mosque was present and that there are no manifestations of objection from the society in Cuiabá regarding the presence of this religious temple during the period of its construction and inauguration.